Building salutogenic capacity: a year of experience from a salutogenic talk-therapy group. Issue 5 (19th October 2016) - Langeland, Eva; Gjengedal, Eva; Vinje, Hege Forbech
Abstract: The primary aim of this paper was to explore and increase knowledge about health-promoting processes among individuals participating in a salutogenic talk-therapy group using a qualitative explorative design. Data were collected through 11 individual interviews and one focus group interview. The informants were five women and two men participating in a salutogenic talk-therapy group over a period of one year. A general structure was identified as 'A richer life', which consisted of three main analysis-derived themes: 'A well-functioning group', 'Who am I?', 'A community of like-minded individuals'. The main impression provided by these data is that although participants expressed their suffering and struggles with mental health problems, attending the group positively affected their lives and well-being. A good salutogenic group climate with high quality of social support, a redefinition of tension, and active participation seem crucial for initiating and promoting salutogenic processes.